Light Tetraquark State Candidates - Zhi-Gang Wang (Advances in High Energy Physics)
In this article, we study the axialvector-diquark-axialvector-antidiquark type scalar, axialvector, tensor, and vector sss¯s¯ tetraquark states with the QCD sum rules. The predicted mass mX=2.08±0.12 GeV for the axialvector tetraquark state is in excellent agreement with the experimental value 2062.8±13.1±4.2 MeV from the BESIII collaboration and supports assigning the new X state to be a sss¯s¯ tetraquark state with JPC=1+−. The predicted mass mX=3.08±0.11 GeV disfavors assigning ϕ2170 or Y2175 to be the vector partner of the new X state. As a byproduct, we obtain the masses of the corresponding qqq¯q¯ tetraquark states. The light tetraquark states lie in the region about 2 GeV rather than 1 GeV.